Evaluasi Aksesisbilitas Website Eka Hospital Bagi Penyandang Disabilitas - Geeriza Vittoria Telaumbanua (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Nowadays, there are more and more ways for PR practitioners to disseminate information to the public. One way is to use a website. This research aims to describe the results of evaluating the accessibility of the ekahospital.com website using various tools such as webaccessibility.com, wave.webaim.org, and powermapper.com. The research method used by the author is qualitative with an exploratory study method approach. After evaluating the Eka Hospital website using several web accessibility checking tools such as webaccessibility.com, wave.webaim.org, and powermapper.com, it was found that the ekahospital.com website was not accessible enough for people with disabilities. The accessibility figure on the Eka Hospital website is only 81%, where the minimum figure for a website to be considered an accessible website is 85%.